Risk of stroke and retinopathy during GLP-1 receptor agonist cardiovascular outcome trials: An eight RCTs meta-analysis - Wei, Jinjing; Yang, Bing; Wang, Ruxin; Ye, Haowen; Wang, Ying; Wang, Lihong; Zhang, Xiaofang (Frontiers in Endocrinology, 2022)
Purpose To explore the risk of stroke (including ischemic and hemorrhagic stroke) in type 2 diabetes mellitus treated with glucagon-like peptide 1 receptor agonist (GLP-1RA) medication according to data from the Cardiovascular Outcome Trials(CVOT). Methods Randomized controlled trials (RCT) on GLP-1RA therapy and cardiovascular outcomes in type 2 diabetics published in full-text journal databases such as Medline (via PubMed), Embase, Clinical Trials.gov, and the Cochrane Library from establishment to May 1, 2022 were searched. We assess the quality of individual studies by using the Cochrane risk of bias algorithm. RevMan 5.4.1 software was use for calculating meta- analysis. Results A total of 60,081 randomized participants were included in the data of these 8 GLP-1RA cardiovascular outcomes trials. Pooled analysis reported statistically significant effect on total stroke risk[RR=0.83, 95%CI(0.73, 0.95), p=0.005], and its subtypes such as ischemic Stroke [RR=0.83, 95%CI(0.73, 0.95), p=0.008] from treatment with GLP-1RA versus placebo, and have no significant effect on the risk of hemorrhagic stroke[RR=0.83, 95%CI(0.57, 1.20), p=0.31] and retinopathy [RR=1.54, 95%CI(0.74, 3.23), p=0.25] Conclusion GLP-1RA significantly reduces the risk of ischemic stroke in type 2 diabetics with cardiovascular risk factors.